Implementation of ERP ( Engange, Research, Present) Intructional Model Using Virtual Laboratory in Science Learning to Increase Student’s Science Process Skills - Siswanto Siswanto; Wartini Wartini; Ahmad Muhlisin; Rina Rahayu; Fifit Firmadani (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The purpose of this study is to analyze the differences in the improvement of science process skills between students whose learning process uses a virtual laboratory-based ERP learning model compared to using discovery learning learning models at SMP Negeri 2 Magelang. This study uses a quasi-experimental method , with a nonequivalent control group design. The result of this study is that there are differences in the improvement of science process skills between classes that apply the ERP learning model ( Engange, Research, Present ) using a virtual laboratory compared to the discovery learning model . The increase in science process skills ( N-gain ) in the class that applies the ERP model using a virtual laboratory is 0.50 with a medium improvement category. The increase in science process skills ( N-gain ) in the class that applies the discovery learning model is 0.29 with a low improvement category. Keywords : ERP Learning Model ( Engange, Research, Present ), Virtual Laboratory, Science Process Skills